Butyrate Enhances Desensitization Induced by Oral Immunotherapy in Cow’s Milk Allergic Mice - Marlotte M. Vonk; Bart R. J. Blokhuis; Mara A. P. Diks; Laura Wagenaar; Joost J. Smit; Raymond H. H. Pieters; Johan Garssen; Léon M. J. Knippels; Betty C. A. M. van Esch (Mediators of Inflammation)
Background. In previous studies, we showed that a fructo-oligosaccharide- (FOS-) supplemented diet enhanced oral immunotherapy (OIT) efficacy in a mouse model for cow’s milk allergy. Fermentation of FOS by intestinal bacteria leads to production of short-chain fatty acids (SCFA) including butyrate. Aim. To investigate the contribution of butyrate in the enhanced efficacy of OIT + FOS. Methods. C3H/HeOuJ mice were sensitized and received OIT with or without FOS or butyrate supplementation. After treatment, whole blood was collected to conduct a basophil activation test (BAT) and allergen challenges were performed to measure acute allergic symptoms. CD4 + CD25 + regulatory T cells (Tregs) were isolated from treated mice or differentiated in vitro and used in a bone marrow-derived mast cell (BMMC) suppression assay. Cecum content was collected to analyze SCFA concentrations. Results. Allergen-induced basophil activation was reduced in OIT + butyrate samples compared to OIT. Accordingly, the acute allergic skin response and mast cell degranulation upon challenge were reduced in OIT + butyrate and OIT + FOS mice compared to sensitized controls. Butyrate was increased in the cecum content of OIT + FOS mice compared to OIT mice and sensitized controls. Treg-mediated BMMC suppression was enhanced after in vivo butyrate and FOS exposure in combination with OIT but with a more pronounced effect for butyrate. Conclusion. Butyrate supplementation enhanced OIT-induced desensitization of basophils and mast cells and Treg functionality. Only OIT + FOS treatment induced potential microbial alterations, shown by increased butyrate levels in cecum content. Both butyrate and FOS are promising candidates to improve OIT efficacy in human studies to treat food allergies.